Antimicrobials from human skin commensal bacteria protect against Staphylococcus aureus and are deficient in atopic dermatitis - Nakatsuji, Teruaki; Chen, Tiffany H; Narala, Saisindhu; Chun, Kimberly A; Two, Aimee M; Yun, Tong; Shafiq, Faiza; Kotol, Paul F; Bouslimani, Amina; Melnik, Alexey V; Latif, Haythem; Kim, Ji-Nu; et al. (Science translational medicine, 2017)
The microbiome can promote or disrupt human health by influencing both adaptive and innate immune functions. We tested whether bacteria that normally reside on human skin participate in host defense by killing , a pathogen commonly found in patients with atopic dermatitis (AD) and an important factor that exacerbates this disease. High-throughput screening for antimicrobial activity against was performed on isolates of coagulase-negative (CoNS) collected from the skin of healthy and AD subjects. CoNS strains with antimicrobial activity were common on the normal population but rare on AD subjects. A low frequency of strains with antimicrobial activity correlated with colonization by The antimicrobial activity was identified as previously unknown antimicrobial peptides (AMPs) produced by CoNS species including and These AMPs were strain-specific, highly potent, selectively killed , and synergized with the human AMP LL-37. Application of these CoNS strains to mice confirmed their defense function in vivo relative to application of nonactive strains. Strikingly, reintroduction of antimicrobial CoNS strains to human subjects with AD decreased colonization by These findings show how commensal skin bacteria protect against pathogens and demonstrate how dysbiosis of the skin microbiome can lead to disease.